School assets and bullying in Chinese youth: A multiple mediation model of intentional self-regulation and internet gaming disorder - Gan, Xiong; Qin, Ke-Nan; Xiang, Guo-Xing; Jin, Xin; Zhu, Cong-Shu (Frontiers in Pediatrics, 2022)
Bullying is a severe social problem affecting young people all over the world. Previous studies have already suggested that engagement in bullying has had massive effects on teenagers’ physical and psychological development. Therefore, investigating the antecedents and underlying mechanisms of this phenomenon is critical and necessary. The present study, based on the developmental assets theory and positive youth development theory, examined the impacts of school assets on adolescent bullying as well as the multiple mediation effects of intentional self-regulation (ISR) and internet gaming disorder (IGD) in the aforementioned relationship. In this study, we adopted a short-term longitudinal design and recruited a sample of 768 Chinese adolescents using a randomized cluster sampling method. The results revealed that T1 school assets significantly and negatively predicted T2 adolescent bullying. Furthermore, T2 ISR and T2 IGD mediated the association between T1 school assets and T2 bullying separately and sequentially. Overall, school resources effectively played a protective role in adolescent development. These current findings contribute to the literature by providing a further understanding of the direct and indirect protective effects of school assets on adolescent bullying. Moreover, practitioners could also benefit from these findings, which assist in preventing and intervening in bullying in the school subsystem.